Cyrtodaria rutupiensis - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Cyrtodaria aff. rutupiensis (Morris, 1852) Fig. 18. Material. —One butterflied specimen (NRM-PZ Mo 183943a–b) with valves opened but still attached, from the upper Paleocene, Zachariassendalen, Spitsbergen, Svalbard. Measurements. —NRM-PZ Mo 183943a–b: L, 43 mm; H, 16.9 mm; W, 5.4 mm. Description. —Shell elongate, weakly inflated, edentulous, moderately thick, covered with commarginal growth lines. Umbones positioned roughly mid-hinge line, not prominent, dorsal margin composed of two straight, weakly inclined, anterior and posterior sections. Anterior and posterior shell margins rounded, gaping; anterior somewhat more rounded than posterior. Ventral shell margin straight with very weak sinus close to mid-line. Anterior adductor muscle scar teardrop-shaped, elongated along anterodorsal margin. Posterior adductor muscle scar shorter but precise shape unknown. Remarks. —Elongate bivalves with a medially positioned umbo and a shape similar to the specimen of Cyrtodaria aff. rutupiensis (Morris, 1852) figured herein were previously described and figured from the Paleocene of Fossildalen as belonging to at least three species of Solecurtus Blainville, 1824, by Hägg (1925: pl. 6: 25–27). As those specimens have no visible transverse ornament characteristic of species of Solecurtus (Hägg 1925: pl. 6: 27), they likely do not belong to Solecurtus and could be assigned to Cyrtodaria . Livšic (1974) mentioned Cyrtodaria sp. occurring in the “Storvola Formation”, an obsolete name for the Eocene Aspelintoppen Formation (Dallmann 1999) overlying the Basilika Formation. Since Livšic (1974) did not provide any figures, we are unable to relate our material to his report. Cyrtodaria rutupiensis (Morris, 1852), a common species occurring in Paleocene deposits of western Spitsbergen (Strauch 1972), the Thanet Formation in Kent, UK (Ward 1978), the Prince Creek Formation in northern Alaska (Marincovich 1993), and the Mount Moore Formation of Ellesmere Island in Arctic Canada (Marincovich and Zinsmeister 1991), is very similar to the ...